Assessment of attitudes towards bioenergy by forestry experts in the Republic of Karelia - Trishkin, Maxim; Lopatin, Eugene; Gavrilova, Olga (Alue- ja ympäristötutkimuksen seura, 2017)
The Republic of Karelia is situated in the northwestern part of Russia and represents approximately 1 %of the country’s territory. Forests cover 53 % of the total area, with 70 % of the total forest area availablefor harvesting. The bioenergy sector is relatively significant as it contributes 10 % to the total energy supplyin Karelia, which as a fossil fuel deficient region is highly dependent on imported energy resources fromother regions of the country. Therefore, the purpose of the study was to assess the role and position ofbioenergy in the Republic of Karelia. It was done by exploring the perception of forestry professionalsand forestry students towards bioenergy production in comparison with other forest uses. The role andposition of bioenergy was identified through the assessment of the importance of landscape elements,ranking of adverse environmental effects on surrounding landscapes, input to the local economy andimportance in planning principles. The results indicate that bioenergy production is perceived to have alow negative effect on the surrounding environment but also a low economic input to the local economyof the region. In addition, bioenergy is perceived to have a low influence on planning principles accordingto the opinions of the respondents. Statistically significant differences were found between the opinions ofrespondents with different occupations in regards to the main factors that negatively affect the surroundingenvironment. In general, the respondents indicated that bioenergy production is of moderate importance,although more research is needed in this field.